2006
DOI: 10.1002/neu.20339
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation promotes peripheral axon regeneration by enhanced neuronal neurotrophin signaling

Abstract: Electrical stimulation of cut peripheral nerves at the time of their surgical repair results in an enhancement of axon regeneration. Regeneration of axons through nerve allografts was used to evaluate whether this effect is due to an augmentation of cell autonomous neurotrophin signaling in the axons or signaling from neurotrophins produced in the surrounding environment. In the thy-1-YFP-H mouse, a single one hour application of electrical stimulation at the time of surgical repair of the cut common fibular n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
88
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(92 citation statements)
references
References 41 publications
4
88
0
Order By: Relevance
“…The use of autografts is often limited because of graft availability and donor-site morbidity. Acellular nerve allograftstissue engineering nerve grafts of natural peripheral nerve extracellular matrix-are used extensively (English et al 2007;Hu et al (2007); Kim et al (2004). Our former study showed that acellular nerve allografts, treated by hypotonic-chemical detergent (Liu et al 2003), had good biocompatibility and could repair the 10 mm gap of the sciatic nerve in the rat and promote nerve regeneration.…”
Section: Discussionmentioning
confidence: 98%
“…The use of autografts is often limited because of graft availability and donor-site morbidity. Acellular nerve allograftstissue engineering nerve grafts of natural peripheral nerve extracellular matrix-are used extensively (English et al 2007;Hu et al (2007); Kim et al (2004). Our former study showed that acellular nerve allografts, treated by hypotonic-chemical detergent (Liu et al 2003), had good biocompatibility and could repair the 10 mm gap of the sciatic nerve in the rat and promote nerve regeneration.…”
Section: Discussionmentioning
confidence: 98%
“…A variety of materials, including synthetic and natural materials have attempted to be employed to bridge nerve defects (Evans et al 2002;Keilhoff et al 2003; Smith et al 2004). ANA with component of natural peripheral nerve extracellular matrix are used extensively (Kim et al 2004;English et al 2007;Hu et al 2007). Our former study showed that acellular nerve allografts with preserved basal lamina tubes, treated by hypotonic-chemical detergent (Liu et al 2003), had good biocompatibility and could repair the 10 mm gap of the sciatic nerve in the rat.…”
Section: Discussionmentioning
confidence: 99%
“…English et al showed that if the environment surrounding regenerating axons in peripheral nerves is made deficient in the trkB ligand NT-4/5 by repairing cut nerves with grafts from NT-4/5 mice, the growth of regenerating axons is markedly reduced [17,18]. The explanation of these findings is that the increase in neuronal BDNF and trkB, which is thought to accompany electrical stimulation, forms the basis for a cell autonomous regulation of axon growth [9].…”
Section: Discussionmentioning
confidence: 92%